Innovation of sleeve packaging with carrier in food industry / Nurul Fatin Alia Borhan ... [et al.] - Borhan, Nurul Fatin Alia; Omar, Mastura; Rosnan, Shalida; Abu Daud, Jamil Iswan; Masod, Muhammad Yusuf (Universiti Teknologi MARA, Kedah, 2023)
According to Puan Fauhan Binti Rosli founder of company Ann Sushiholic is opened in 23 January 2019 which is located in Kompleks Perniagaan Masjid Tuanku Syed Putra, Kangar Perlis. This company use the plastic container to pack the Sushi and then they put it in a plastic bag. They don’t has specific box packaging for Sushiholic. The role of the packaging is to protect the product itself and by the same time it can be display with attractive branding design to convince to the customer of product quality. The package becomes a vital factor in the buying choice because it communicate to the consumer during the decision making time. This prototype featuring an innovation design where it can be simply fold into flat for storing purpose, placing chopstick on the side of packaging and food can be seen through transparent container while placing the packaging on containers. Sustainability has emerged as a core design concept in packaging development to minimize environmental impacts, maximize cost saving and avoid excessive or deceptive packaging. The additional combination of augmented reality (AR) technology for the latest technology requires an interactive and highly dynamic experience with today’s smartphones to be on the any platform. In addition, the combination with the QR code make it easy to get information just pick up the phone to scan the QR code found in the sleeve packaging.